The running pattern and its importance in running long-distance gears - Jarosław Hoffman; Anna Lewandowska; Dorota Ratuszek-Sadowska; Anetta Hoffman; Monika Kuczma; Paweł Landowski; Magdalena Hagner-Derengowska (Kazimierz Wielki University, 2017)
The running pattern is individual for each runner, regardless of distance. We can characterize it as the sum of the data of the runner (age, height, training time, etc.) and the parameters of his run. Building the proper technique should focus first and foremost on the work of movement coordination and the power of the runner. In training the correct running steps we can use similar tools as working on deep feeling. The aim of this paper was to define what we can call a running pattern, what is its influence in long-distance running, and the relationship between the training technique and the running pattern. The importance of a running pattern in long-distance racing is immense, as the more distracted and departed from the norm, the greater the harm to the body will cause it to repetition in long run. Putting on training exercises that shape the technique is very important and affects the running pattern significantly.